(untitled) (Global Journal of Management and Business Research, 2011)
Increasingly organizations are realizing that they have to establish an equitable balance between the employee s contribution to the organization and the organization s contribution to the employee Establishing this balance is one of the main reasons to reward employees Organizations that follow a strategic approach to creating this balance focus on the three main components of a reward system which includes compensation benefits and recognition Studies that have been conducted on the topic indicates that the most common problem in organizations today is that they miss the important component of Reward which is the low-cost high-return ingredient to a well-balanced reward system A key focus of recognition is to make employees feel appreciated and valued Research has proven that employees who get recognized tend to have higher self-esteem more confidence more willingness to take on new challenges and more eagerness to be innovative The aim of this study is to investigate whether rewards and recognition has an impact on employee motivation A biographical and Work Motivation Questionnaire was administered to respondents The results also revealed that staff and employees from non-white racial backgrounds experienced lower levels of rewards and motivation Future research on the latter issues could yield interesting insights into the different factors that motivate employees Notwithstanding the insights derived from the current research results need to be interpreted with caution since a convenience sample was used thereby restricting the generalisability to the wider population